Management of Solid Hazardous and Toxic Waste (LB3) in Puskesmas, Tulungagung District - Indasah; Wiji Astuti; Prima Dewi Kusumawati; Suryanti, Venty (Universitas STRADA Indonesia, 2022)
Public Health Center waste is considered as a link in the chain of transmission of infectious diseases. Waste can contain toxic chemicals and sharp objects that can cause health problems and injuries. The purpose of this study was to explore the management of solid hazardous and toxic waste (LB3) at the Tulungagung District Health Center. The design of this study was qualitative research with a phenomenological approach with a research focus directed at exploring the management of solid hazardous and toxic waste (LB3) at the Tulungagung District Health Center. In addition, with a qualitative approach it is hoped that the situation and problems encountered in the activity can be disclosed. The informants in this study were 22 (twenty two) Sanitarians in the Public Health Center with source triangulation. The management of solid Hazardous and Toxic Waste (LB3) at the Tulungagung District Health Center is quite good, where in terms of sorting the health center has implemented the standards that apply at the local health office, namely by preparing separate containers and containers that are safe from any contamination, then in terms of storage the health center has also implemented an effective storage system. However, there are some drawbacks starting from transportation, where in terms of transportation to the destruction of waste, most health centers cooperate with third parties, however, transportation is carried out by parties when it is not in accordance with standards where there is often a delay in transporting waste so that it accumulates in the environment for some time health center, apart from that during transport it also keeps the health center workers busy by collecting them outside of the health center working hours.